2010
DOI: 10.3109/03639040903117348
|View full text |Cite
|
Sign up to set email alerts
|

Critical evaluation of permeation enhancers for oral mucosal drug delivery

Abstract: To optimize the concentration of enhancer to limit its toxicity while facilitating an enhancing effect reproducibly will be a big challenge for future developments. Advances in permeability modulation and formulation with appropriate enhancers can provide for effective and feasible buccal drug delivery for many drugs, which otherwise have to be injected or ingested with water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
43
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(43 citation statements)
references
References 180 publications
0
43
0
Order By: Relevance
“…Several models for assessing drug permeability through oral mucosa are known, however, they lack the mucus layer. Permeability across excised mucosal tissue can be studied in side-by-side diffusion cells such as modified Ussing chambers or Franz cells [7]. To the authors' knowledge it has not been confirmed that the mucus layer on the epithelium is intact after handling the excised tissue [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several models for assessing drug permeability through oral mucosa are known, however, they lack the mucus layer. Permeability across excised mucosal tissue can be studied in side-by-side diffusion cells such as modified Ussing chambers or Franz cells [7]. To the authors' knowledge it has not been confirmed that the mucus layer on the epithelium is intact after handling the excised tissue [8].…”
Section: Introductionmentioning
confidence: 99%
“…ibuprofen) with high log P and has been employed to achieve different drug release profiles [13][14][15][16]. Previous studies have shown that the erosion of poloxamer-based gels, in aqueous media, is relatively fast and it also exhibits mucosal permeation enhancing properties [17]. Plasticizers employed were polyethylene glycol 600 (Figure 1(c)) which is a hydrophilic polymer constituted of oxyethylene monomers [18] and glycerol (Figure 1(d)), with three hydroxyl groups, that dissolves in water and disrupts the hydrogen bonding between carrageenan chains.…”
Section: Introductionmentioning
confidence: 99%
“…27 Other agents such as ionic surfactants have demonstrated increases in epithelial permeability, but they have been shown to illicit toxic and irritative potential at relatively low concentrations. 28 Although these chemical permeability enhancements have shown enhanced delivery effects, there are permanent toxicity risks that must be addressed. Therefore, the use of nanostructured thin films to induce large molecule transport across the epithelial barrier presents a significant finding for translational drug delivery applications.…”
mentioning
confidence: 99%